(untitled) (Acta Scientiarum. Health Sciences, 2016)
The objective was to identify conditions for the discontinuation of exclusive breastfeeding. This is a qualitative study developed in a Primary Health Care Unit (PHCU) in Fortaleza, Ceará, Brazil. It included 20 mothers of children aged 0-6 months old who were breastfeeding. The reports evidenced three categories: Guidance received during prenatal care; Meanings of breastfeeding; Determinants of early weaning. It can be concluded that part of the determinants of early weaning is in the building of or failure to build knowledge about breastfeeding. Cultural concepts or myths are inadequate and socially reproduced due to failure, on the part of health professionals who assist expectant mothers during prenatal care or those who assist postpartum women, to deconstruct them.